A randomized clinical trial comparing metabolic parameters after 48 weeks of standard‐ and low‐dose stavudine therapy and tenofovir disoproxil fumarate therapy in HIV‐infected South African patients. Issue 1 (28th August 2013) - Menezes, CN; Crowther, NJ; Duarte, R; Van Amsterdam, D; Evans, D; Dickens, C; Dix‐Peek, T; Rassool, M; Prinsloo, A; Raal, F; Sanne, I
<x xml:space="preserve">Abstract</x> Objectives Low‐dose stavudine therapy may have a lower toxicity profile compared with standard dose. A randomized controlled trial comparing these two doses of stavudine with tenofovir disoproxil fumarate (tenofovir DF) was performed to assess the effects on anthropometry, markers of inflammation, and lipid and glucose metabolism in Black South African patients. Methods Sixty patients were randomized 1:1:1 to either standard‐dose (30–40 mg) or low‐dose (20–30 mg) stavudine or tenofovir DF (300 mg), each combined with lamivudine and efavirenz, for 48 weeks. Anthropometry, markers of inflammation, and lipid and glucose metabolism were assessed using standard techniques. Results In all three treatment arms, there was a significant increase in lipid levels over the study period. At 48 weeks, fasting glucose level (P < 0.005) and homeostasis model assessment (HOMA) score (P < 0.05) increased significantly in the standard‐dose stavudine arm, as did insulin and C‐peptide levels in both the standard‐ and low‐dose stavudine arms. At week 48, a significant decrease (P < 0.05) in adiponectin was noted in the standard‐dose stavudine arm, but there was an increase (P < 0.005) in the tenofovir DF arm. In both the stavudine arms, significant increases in anthropometric measures occurred at 24 weeks but these decreased by week 48. Mitochondrial toxicities occurred in both the stavudine arms. Immunological and virological outcomes were similar for all three arms. Conclusions This study highlights the occurrence of metabolic abnormalities with both stavudine and tenofovir DF treatment. Awareness of the potential increased cardiovascular risk should be of concern with the use of both these therapies.